Penerapan Branding Dan Digital Marketing Guna Pengembangan Umkm Kelurahan Klampok Kota Blitar - Wijayanti, Annisa Rizky; Nur, Dhani Ichsanuddin (CV. ITTC INDONESIA, 2023)
MSME actors need to pay attention to branding and digital marketing in running and managing their business. Branding can be used as a business identity, while digital marketing can be used for online sales and marketing. However, not all MSME actors can do good branding and make the best use of digital platforms to develop their businesses. Therefore, group 33 held branding and digital marketing outreach in the Klampok sub-district, Blitar city, which aims to provide knowledge, insight and information about branding and digital marketing. The methods used in this activity are observation and interviews as well as outreach and discussion. This socialization invited resource persons from the UKM and Naker cooperative services as extension speakers. By holding this socialization, it will provide benefits and new knowledge to MSME actors so they can manage their business by implementing and creating new branding and can apply the use of online media to carry out sales and marketing.